SISTEM KONTROL DAN MONITORING SMART HOUSE BERBASIS IoT DENGAN SMARTPHONE ANDROID - Alamsyah, Gharisa Nur; Winardi, Slamet (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2022)
Smart house is one of the automatic home control systems that can provide comfort to homeowners to control electronic devices and monitor room security using an android smartphone. The concept of a smart house is a system that is intended for homes so that we can live comfortably. The application of the smart house concept aims to regulate electronic equipment and monitor security and temperature in our homes. With the development of technology, we can take advantage of smartphone android as a smart house control tool. Switch systems can be replaced by using relay devices and security systems can be installed using reed switch sensors, temperature monitoring systems can be installed using temperature sensors and all of these tools can be controlled and monitored through a network-based microcontroller device so that it can be connected to an installed smartphone. smart house control and monitoring program.